# How do you solve \frac { 2 k + 5} { 5} + 9= - ( k - 3)?

##### 2 Answers
Oct 14, 2017

$k = - 5$

Refer to the explanation for the process.

#### Explanation:

Solve:

$\frac{2 k + 5}{5} + 9 = - \left(k - 3\right)$

Expand the right side.

$\frac{2 k + 5}{5} + 9 = - k + 3$

Subtract $9$ from both sides.

$\frac{2 k + 5}{5} = - k + 3 - 9$

Simplify.

$\frac{2 k + 5}{5} = - k - 6$

Multiply both sides by $5$.

$2 k + 5 = 5 \left(- k - 6\right)$

Simplify.

$2 k + 5 = - 5 k - 30$

Subtract $5$ from both sides.

$2 k = - 5 k - 30 - 5$

Simplify.

$2 k = - 5 k - 35$

Add $5 k$ to both sides.

$2 k + 5 k = - 35$

Simplify.

$7 k = - 35$

Divide both sides by $7$.j

$k = - \frac{35}{7}$

Simplify.

$k = - 5$

Oct 14, 2017

$k =$-5

#### Explanation:

Taking L C M and removing bracket in R H S,
$\frac{2 k + 5 + 45}{5} = - k + 3$

$2 k + 50 = - 5 k + 15$ Cross multiplying and simplifying LHS,

$2 k + 5 k = - 50 + 15$ Bringing k terms to LHS and constants to RHS.

$7 k = - 35$

$k = \frac{- 35}{7} =$-5